Greece - Miller, Korina; Armstrong, Kate; Averbuck, Alexis; Bain, Carolyn; Clark, Michael Stamatios; Isalska, Anita; Kaminski, Anna; Ward, Greg; Waters, Richard (Carlton, Victoria, Australia Lonely Planet Publications Pty Limited, 2016)
"Lonely Planet Greece is your passport to the most relevant, up-to-date advice on what to see and skip, and what hidden discoveries await you. Roam through the hilltop ruins of the Acropolis, climb to the monastery-capped rock pinnacles of Meteora, or ferry across to one of the breathtakingly beautiful islands; all with your trusted travel companion. Get to the heart of Greece and begin your journey now!"
At head of title: Lonely Planet.
Includes Athens pull-out map, expert recommendations, local secrets.
Includes bibliographical references and index.
Keywords: Greece -- Guidebooks; Greece -- Description and travel